2014
DOI: 10.1016/j.finmar.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

How should individual investors diversify? An empirical evaluation of alternative asset allocation policies

Abstract: This paper evaluates numerous diversification strategies as a possible remedy against widespread costly investment mistakes of individual investors. Our results reveal that a very broad range of simple heuristic allocation schemes offers similar diversification gains, as well-established or recently developed portfolio optimization approaches. This holds true for both international diversification in the stock market and diversification over different asset classes. We thus suggest easy-to-implement allocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 73 publications
4
64
0
Order By: Relevance
“…It can also be observed that the correlation coefficients reported in Table 2 between each of the African countries and SandP Dow Jones index are not significance. This corresponds and affirms the argument that the stock returns of African (developing) economies and that of the developed, which is represented by SandP Dow Jones are not related to each other (Jacobs et al, 2014;Bekaert and Harvey, 1997a). Hence foreign investors may be exposed to higher investment opportunities if they invest and diversify in Africa.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…It can also be observed that the correlation coefficients reported in Table 2 between each of the African countries and SandP Dow Jones index are not significance. This corresponds and affirms the argument that the stock returns of African (developing) economies and that of the developed, which is represented by SandP Dow Jones are not related to each other (Jacobs et al, 2014;Bekaert and Harvey, 1997a). Hence foreign investors may be exposed to higher investment opportunities if they invest and diversify in Africa.…”
Section: Resultssupporting
confidence: 84%
“…Using data availability as criteria, only 11 countries were captured in our sample. This study also focuses on these 11 countries because they may offer better investment opportunities and portfolios with high returns (Groot et al, 2012;Jacobs et al, 2014). In computing the stock returns, the monthly stock price indices of each country are used.…”
Section: Source Of Data and Methodologymentioning
confidence: 99%
“…Mean variance optimisation is based on the Modern Portfolio Theory (MPT) outlined in Markowitz, (1952). There is considerable literature on portfolio construction, some empirical studies are critical of mean variance optimisation (De Miguel et al, (2009), Jacobs et al,. (2014).…”
Section: Resultsmentioning
confidence: 99%
“…The increasing correlations drive portfolio mana gers to search for fresh alternative assets that will provide the required diversification for their portfolios (Das et al 2013). Diversification benefits tend to be especially prominent in times of unexpected inflation and declining stock markets (Jacobs et al 2014). Of course, diversification does not gu arantee a profit or eliminate the risk of loss (Wilson 2014).…”
Section: Consideration Of Investment Portfolio Diversificationmentioning
confidence: 99%